Ambulatory anomaly in the ancient Iberia. ‘Monosandals’, injured heroes and young dancers - Grau Mira, Ignasi; Crespo Mas, Teodoro (Gerión. Revista de Historia Antigua, 2013)
In this paper we analyze some elements of the Iberian iconography related to the general subject of the ambulatory anomaly, which are frequent in the Ancient Mediterranean. These themes are the monosandals, the injuries in the leg of the hero and dances of young people. In our opinion, these Iberian representations are related to ritual practices well documented in the Ancient Mediterranean. This relationship illustrates the high degree of contact between the Iberian and the Mediterranean World and the feasible existence of a common cultural character or koiné.
Keywords: Iberian Culture; Mythology; Iconography; Initiation; Ambulatory anomaly.